RFID-Based Warehouse Management System for Improving Inventory Accuracy and Operational Efficiency - Akhmad, Ekka Pujo Ariesanto; Prawirosastro, Carlos Lazaro (Universitas Hang Tuah, 2026)
Warehouse operations are increasingly required to deliver high levels of accuracy, speed, and real-time visibility in response to growing supply chain complexity and customer expectations. However, conventional barcode-based warehouse management systems remain constrained by line-of-sight scanning, sequential data capture, and heavy reliance on manual intervention, which often lead to inventory inaccuracies and operational inefficiencies. This study investigates the implementation of Radio Frequency Identification (RFID) technology integrated with a Warehouse Management System (WMS) to enhance inventory accuracy and operational performance in warehouse environments. Using a case-based experimental research design, the study compares warehouse performance before and after RFID implementation across key processes, including receiving, storage, picking, and shipping. Operational data were collected through time studies, inventory audits, and error tracking under comparable workload conditions. The results demonstrate that RFID integration significantly improves overall inventory accuracy, reduces processing time by more than half, and decreases operational error rates by approximately eighty percent compared to a conventional barcode-based system. These improvements are primarily driven by automatic, non-line-of-sight, and simultaneous data capture enabled by RFID, which minimizes human intervention and ensures real-time synchronization between physical goods movement and digital inventory records. This research contributes empirical system-level evidence on the performance impact of RFID-enabled warehousing and proposes an integrated RFID–WMS implementation framework that supports end-to-end warehouse operations. The findings provide both theoretical insights and practical guidance for organizations seeking to adopt RFID as a foundation for smart warehouse transformation.